ANALISIS PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (STUDY KASUS PADA PT. SONY MOBILE INDONESIA-CAB SEMARANG) - Kholid Farid (STIE Pelita Nusantara Semarang, 2017)
Compensation and working discipline is important relationships in employee performance, compensation will encourage employees to work better and work discipline that will produce good work also in improving employee performance. This study aimed to analyze the effect of compensation and working discipline to employees performance at PT.Sony Mobile Indonesia Semarang branch.The population of this study were 65 respondents and sample research that all of the population of 65 respondents. So this research is called the study population or census study. The variables in this study is divided into two variables, independent variables and the dependent variable. The independent variables consist of compensation and working discipline, and the dependent variable is the performance of employees. Data collection method used is using a questionnaire method. Data analysis tools used include validity, reliability test, t-test, f, and the coefficient of determination.The results showed that the partial (people) there is a positive and significant influence between compensation (X1) on employee performance (Y); partially (people) there is a positive and significant influence between work discipline (X2) on employee performance (Y). The test results showed that the variable compensation (X1), and discipline (X2) simultaneously (together) a positive and significant influence on employee performance (Y).